The effect of rootstock on the nectar production of apple cultivar `Idared’ - Nagy Tóth, E.; Orosz-Kovács, Zs. (International Journal of Horticultural Science, 2001)
Approaches based on the daily rhythm of apple flowers provide a new stage in nectar research, where the synchronous functioning of sexual organs is studied. In the flower biological studies the insect attraction of flowers was also studied. The two most important factors of insect attraction are the pollen- and nectar production of the flowers. From 1993 to 1998 we studied the food, that flower had to offer for the pollinating insects at different times of the day. Studies were carried out on ’Idared’, one of the hybrids of ’Jonathan’ apple cultivar. The fruit of ’Idared’ is bigger than the fruit of `Jonathan’. It is bright red, transportable, has a bigger productivity and is not subject to Jonathan-spots. Concerning its inner characteristics, it is juicy, the flesh consistency is better than that of ’Jonathan’, but its acid/sugar ratio is worse (Sansavini et al. 1981).